COVID-19 Infection Induce miR-371a-3p Upregulation Resulting in Influence on Male Fertility - Heike Goebel; Barbara Koeditz; Manuel Huerta; Ersen Kameri; Tim Nestler; Thomas Kamphausen; Johannes Friemann; Matthias Hamdorf; Timo Ohrmann; Philipp Koehler; Oliver A. Cornely; Manuel Montesinos-Rongen; et al. (Biomedicines, 2022)
In December 2019, the first case of COVID-19 was reported and since then several groups have already published that the virus can be present in the testis. To study the influence of SARS-CoV-2 which cause a dysregulation of the androgen receptor (AR) level, thereby leading to fertility problems and inducing germ cell testicular changes in patients after the infection. Formalin-Fixed-Paraffin-Embedded (FFPE) testicular samples from patients who died with or as a result of COVID-19 (n = 32) with controls (n = 6), inflammatory changes (n = 9), seminoma with/without metastasis (n = 11) compared with healthy biopsy samples (n = 3) were analyzed and compared via qRT-PCR for the expression of miR-371a-3p. An immunohistochemical analysis (IHC) and ELISA were performed in order to highlight the miR-371a-3p targeting the AR. Serum samples of patients with mild or severe COVID-19 symptoms (n = 34) were analyzed for miR-371a-3p expression. In 70% of the analyzed postmortem testicular tissue samples, a significant upregulation of the miR-371a-3p was detected, and 75% of the samples showed a reduced spermatogenesis. In serum samples, the upregulation of the miR-371a-3p was also detectable. The upregulation of the miR-371a-3p is responsible for the downregulation of the AR in SARS-CoV-2-positive patients, resulting in decreased spermatogenesis. Since the dysregulation of the AR is associated with infertility, further studies have to confirm if the identified dysregulation is regressive after a declining infection.